Pengolahan Bahan Makanan Campuran (BMC) Sebagai Pengisi Makanan Jajanan untuk Anak Sekolah Dasar - S. Widowati; A.F. Rochmadi; L. Kustiyah; D.S. Slamet; D.S. Darmadjati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1999)
Three formules of composite flour were prepared in this research, comprising : 1 fermented taro-corn-soybean, II. fermented taro-corn-germinated soybean, and III. fermented taro-corn-soybean cake. The formules were used as titter for traditional snack food processing. The products were evaluated for their chemical and sensory properties. Result showed that formula I, II, HI contained 26.8, 16.2, 19.8% of protein, 442, 403, 377 ca1/100 g of energy and 17.4, 8.4, 10.9 of NDpE%, respectiveley. Organoleptik test showed that all traditional snack food were acceptable. Consumption of 100 g of snack food contribuded 22.9-41.8% of protein and 19.3 - 22.3% of energy needed by children of 6 - 12 years old, respectively